2018
DOI: 10.3906/tar-1801-78
|View full text |Cite
|
Sign up to set email alerts
|

Application of data mining and adaptive neuro-fuzzy structureto predict color parameters of walnuts (Juglans regia L.)

Abstract: Introduction Walnut (Juglans regia L.) belongs to the family Juglandaceae (Şen, 2011). It ranks third in nut production worldwide after cashews and almonds (Amin et al., 2017). Walnuts are quite rich in oils, proteins, vitamins, fibers, minerals, and antioxidants; thus they are considered quite healthy nuts for human nutrition (Khir et al., 2014). Walnuts are used not only as an individual foodstuff, but also as an ingredient of several baked and processed foods (Eliseeva et al., 2017). The physical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Increasing sphericity was observed with decreasing shape index because the relation between both variables was significant. The results of some scientific studies conducted on walnut and hazelnut cultivars or genotypes by Demir et al (2018), Sayinci et al (2015a), Ercisli et al (2012), and Ozkan and Koyuncu (2005) supported the findings of the current study. The surface area of agricultural products is closely related to evaporation from the product surfaces.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Increasing sphericity was observed with decreasing shape index because the relation between both variables was significant. The results of some scientific studies conducted on walnut and hazelnut cultivars or genotypes by Demir et al (2018), Sayinci et al (2015a), Ercisli et al (2012), and Ozkan and Koyuncu (2005) supported the findings of the current study. The surface area of agricultural products is closely related to evaporation from the product surfaces.…”
Section: Resultssupporting
confidence: 89%
“…The measurements were performed both over the outer surface and on the inside of the shells. The values of CIE-L*, a*, and b* were recorded for all samples; these parameters were also used to calculate color index (CI), hue angle (h*), and chroma (C*) values for the studied samples (McGuire, 1992;Demir, 2018).…”
Section: Color Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sütyemez (2007) investigated the production amounts, flower dust and germination of 32 walnut type under certain conditions. Demir (2018) has developed a new rule (equation) with Prediction and Find Laws algorithms of data mining to calculate colour index (CI) by using an adaptive neuro-fuzzy approach.…”
Section: Introductionmentioning
confidence: 99%
“…Walnut is one of the oldest plants distributed worldwide, ranking third in nut production (Fernandez-Lopez et al, 2000;Ercisli et al, 2012), and is considered to be quite healthy for human nutrition (Khir et al, 2014). It is used not only as an individual foodstuff, but also as an ingredient in several baked and processed foods (Eliseeva et al, 2017), depending on the fruit quality parameters (Warmund, 2008;Fuentealba et al, 2017;Demir, 2018). Amin et al (2017) indicated that walnuts can be useful as potential natural antibacterial agents.…”
Section: Introductionmentioning
confidence: 99%